Association Between ABO Blood Group, Dental Caries, Gingivitis, Impacted Teeth and Malocclusion Among Saudi Adults: A Cross-Sectional Study - Almalki SA; Gowdar IM; Arishi FO; Alhumaidani RK; Alhumaidani FK; Gufran K (Dove Medical Press, 2024)
Sultan Abdulrahman Almalki,1,* Inderjit Murugendrappa Gowdar,1,* Faisal Omar Arishi,2 Rakan Khaled Alhumaidani,2 Faisal Khaled Alhumaidani,2 Khalid Gufran1 1Department of Preventive Dental Sciences, College of Dentistry, Prince Sattam Bin Abdulaziz University, Alkharj, Saudi Arabia; 2College of Dentistry, Prince Sattam Bin Abdulaziz University, Alkharj, Saudi Arabia*These authors contributed equally to this workCorrespondence: Khalid Gufran, Department of Preventive Dental Sciences, College of Dentistry, Prince Sattam bin Abdulaziz University, Alkharj, Saudi Arabia, Tel +00966502294308, Email k.syed@psau.edu.saBackground: Whether there is a relationship between blood group and the likelihood of acquiring oral diseases. Therefore, the present study investigated the potential association between ABO blood groups and various dental conditions, including dental caries, gingivitis, malocclusion, and impacted teeth, in Saudi adults aged 18 years and older.Methods: A cross-sectional study was conducted on 300 participants who met the inclusion criteria. Data collection included assessment of dental caries status using the decayed missing filled teeth (DMFT) and decayed missing filled surfaces (DMFS) indices, evaluation of gingivitis using the Gingival Index, classification of malocclusion according to Angle's classification system, and recording the presence or absence of impacted teeth.Results: The AB blood group had the significantly highest mean DMFS score (8.58± 6.63), while the O blood group had the lowest mean DMFS score (6.37± 4.43). Additionally, blood group O showed a slightly higher prevalence of gingivitis (51.92%) than the other blood groups. Blood group A demonstrated a higher prevalence of both Class II (34.2%) and Class III (19%) malocclusions, with statistically significant differences. Regarding impacted teeth, blood group AB (48.8%) had the highest occurrence.Conclusion: There exists an association between oral disease and ABO blood group in Saudi adults. The results of this study indicate that individuals with specific blood types may be more prone to oral diseases, which can aid in the early diagnosis and prevention of these conditions.Keywords: ABO blood groups, dental caries, gingivitis, malocclusion, impacted teeth